Harmostes Burmeister, 1835 (Hemiptera, Heteroptera, Rhopalidae): new records, with an emphasis in the southernmost region of Brazil - Thaíz Ramos (Pensoft Publishers, 2021)
Harmostes Burmeister, 1835 (Rhopalidae, Rhopalinae) comprises 32 species distributed from Canada to southern South America. From the analysis of material deposited in collections, we identified and diagnosed the species of Harmostes from the state of Rio Grande do Sul. Among the analyzed material, seven species of Harmostes are included, six of them being reported from the state for the first time. The known geographical distribution in other Brazilian regions was also expanded for H. (H.) serratus (Fabricius, 1775) (Amapá, Amazonas, Santa Catarina), H. (N.) apicatus Stål, 1859 (Mato Grosso do Sul), and H. (H.) incisuratus Distant, 1881 (Santa Catarina).